OTORITAS PEMERINTAH DALAM NOVEL PULANG KARYA LEILA S. CHUDORI POSTMODERNISME MICHEL FOUCAULT - Tuflih, Muhammad Alfian; Ridwan, Ridwan; Putra, Pauzan Ramadan (JURNAL SASTRA INDONESIA (SASINDO), 2024)
This research aims to reveal government authority in the novel Pulang by Leila S. Chudori. The author uses data from the novel Pulang through the main character Dimas Suryo and quotes the contents of bloody letters that Dimas received from family, friends, children and other colleagues. The author also describes the cruelty of the New Order government authorities and the PKI towards the people who dared to criticize the anti-PKI government and people. This research uses a qualitative descriptive approach method. A qualitative approach that produces written or verbal data and interprets it according to postmodernism theory. Michel Foucault. The data source in this research is the text contained in the novel Pulang by Leila S. Chudori which is analyzed according to historical aspects and government power at that time. This research uses reading and note-taking techniques for data collection. This research was carried out by identifying, analyzing, describing and drawing conclusions about aspects of history and government power. The author uses objects from the novel Pulang by Leila S. Chudori to describe the situation at that time